Effect of Decaffeinated Green Tea Polyphenols on Body Fat and Precocious Puberty in Obese Girls: A Randomized Controlled Trial - Xie, Luyao; Tang, Qingya; Yao, Die; Gu, Qiuyun; Zheng, Hao; Wang, Xiaodi; Yu, Zhiping; Shen, Xiuhua (Frontiers in Endocrinology, 2021)
Background: Obesity has been reported to be an important contributing factor for precocious puberty, especially in girls. Green tea polyphenols have been shown the effect on weight reduction in adult population, but few related studies have been conducted in children. This study was to examine the effectiveness and safety of decaffeinated green tea polyphenols (DGTP) on ameliorating obesity and early sexual development in girls with obesity. Design: This is a double-blinded randomized controlled trial. Girls with obesity aged 6-10 years old were randomly assigned to receive 400mg/d DGTP or isodose placebo orally for 12 weeks. During this period, all participants received the same instruction on diet and exercise from trained dietitians. Anthropometric measurements, secondary sexual characteristics, B-scan ultrasonography of uterus, ovaries and breast tissues, and related biochemical parameters were examined and assessed pre- and post-treatment. Results: Between August 2018 to January 2020, 62 girls with obesity (DGTP group n=31, control group n=31) completed the intervention and were included in analysis. After the intervention, body mass index, waist circumference, and waist to hip ratio significantly decreased in both groups, but the percentage of body fat (PBF), serum uric acid (UA), and the volumes of ovaries decreased significantly only within the DGTP group. After controlling confounders, DGTP showed a significantly decreased effect on the change of PBF (β=2.932, 95% CI: 0.214 to 5.650), serum UA (β=52.601, 95% CI: 2.520 to 102.681), and ovarian volumes (right: β=1.881, 95% CI: 0.062 to 3.699, left: β=0.971, 95% CI: 0.019 to 1.923) in girls with obesity. No side effect was reported in both groups during the whole period. Conclusion: Decaffeinated green tea polyphenols have shown beneficial effects of ameliorated obesity and postponed early sexual development in girls with obesity without any adverse effects.